Functions and regulation of the MRX complex at DNA double-strand breaks - Elisa Gobbini; Corinne Cassani; Matteo Villa; Diego Bonetti; Maria Pia Longhese (Microbial Cell)
DNA double-strand breaks (DSBs) pose a serious threat to genome stability and cell survival. Cells possess mechanisms that recognize DSBs and promote their repair through either homologous recombination (HR) or non-homologous end joining (NHEJ). The evolutionarily conserved Mre11-Rad50-Xrs2 (MRX) complex plays a central role in the cellular response to DSBs, as it is implicated in controlling end resection and in maintaining the DSB ends tethered to each other. Furthermore, it is responsible for DSB signaling by activating the checkpoint kinase Tel1 that, in turn, supports MRX function in a positive feedback loop. The present review focuses mainly on recent works in the budding yeast Saccharomyces cerevisiae to highlight structure and regulation of MRX as well as its interplays with Tel1.